2009
DOI: 10.1038/leu.2008.372
|View full text |Cite
|
Sign up to set email alerts
|

A new molecular network comprising PU.1, interferon regulatory factor proteins and miR-342 stimulates ATRA-mediated granulocytic differentiation of acute promyelocytic leukemia cells

Abstract: In the acute promyelocytic leukemia (APL) bearing the t(15;17), all-trans-retinoic acid (ATRA) treatment induces granulocytic maturation and complete remission of leukemia. We identified miR-342 as one of the microRNAs (miRNAs) upregulated by ATRA during APL differentiation. This miRNA emerged as a direct transcriptional target of the critical hematopoietic transcription factors PU.1 and interferon regulatory factor (IRF)-1 and IRF-9. IRF-1 maintains miR-342 at low levels, whereas the binding of PU.1 and IRF-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 21 publications
3
78
0
1
Order By: Relevance
“…We showed that a set of miRs, including miR-100, 126, 126*, 181b, 181d, 223, and 342 were consistently up-regulated in CD34 ϩ EB cells, which indicates that these 7 miRs may represent a common feature of hematopoietic differentiation from hESCs. Among them, miRs-126/126*, 29,36 181b, 37 181d, 38 223 30,31 and 342 39 have a well-characterized association with the hematopoietic system and miRs-126/126* are the most highly up-regulated. miR-126 and 126* are processed from the same primary miR and located in an intron of Egfl7, a gene that is highly expressed in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that a set of miRs, including miR-100, 126, 126*, 181b, 181d, 223, and 342 were consistently up-regulated in CD34 ϩ EB cells, which indicates that these 7 miRs may represent a common feature of hematopoietic differentiation from hESCs. Among them, miRs-126/126*, 29,36 181b, 37 181d, 38 223 30,31 and 342 39 have a well-characterized association with the hematopoietic system and miRs-126/126* are the most highly up-regulated. miR-126 and 126* are processed from the same primary miR and located in an intron of Egfl7, a gene that is highly expressed in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…miR-107 has been shown to target the transcription factor NFI-A (Garzon et al, 2007), which participates with C/EBPa in the regulation of granulocyte differentiation-associated miR-223 expression (Fazi et al, 2005). miR-342 has been shown to stimulate granulocytic differentiation (De Marchis et al, 2009). Interestingly, the putative target of miR-342 MEIS1, a member of the TALE family of homeodomain Differentially expressed miRNAs in APL patients S Careccia et al genes, has been shown to have a pivotal role in normal hematopoiesis (Abramovich and Humphries, 2005;Diaz-Blanco et al, 2007) and it is frequently upregulated in human AMLs (Kumar et al, 2009).…”
Section: Differentially Expressed Mirnas In Apl Patientsmentioning
confidence: 99%
“…These findings are supported by the fact that IRF-1 Ϫ/Ϫ mice have defective myelopoiesis, which is partly caused by down-regulation of PU.1, 42 and that infection of neutrophil precursors with Anaplasma phagocytophilum results in down-regulation of both IRF-1 and PU.1. 43 A cooperative function between IRF-1 and PU.1 has been reported during all-trans retinoic acid-mediated granulopoiesis 44 and in IFN-␥-stimulated myeloid cells. 45 Furthermore, IRF-1 is naturally down-regulated toward the final stages of erythroid maturation, 46 which overall sustains the notion that suppression of the IRF-1-PU.1 axis is a prerequisite for normal erythropoiesis.…”
Section: Impact Of Ifn-␥ On the Erythroid Balance 2585mentioning
confidence: 99%